Biological roles of enhancer RNA m6A modification and its implications in cancer - Yangyang Han; Jingqi Sun; Minghui Yao; Liying Miao; Mengjia Li (Cell Communication and Signaling)
Abstract Enhancers, as distal cis-regulatory elements in the genome, have a pivotal influence on orchestrating precise gene expression. Enhancer RNAs (eRNAs), transcribed from active enhancer regions, are increasingly recognized as key regulators of transcription. N6-methyladenosine (m6A), the most plentiful internal modification in eukaryotic mRNAs, has garnered significant research interest in recent years. With advancements in high-throughput sequencing technologies, it has been established that m6A modifications are also present on eRNAs. An accumulative body of evidence demonstrates that aberrant enhancers, eRNAs, and m6A modifications are intimately connected with carcinoma onset, progression, invasion, metastasis, treatment response, drug resistance, and prognosis. However, the underlying molecular mechanisms governing m6A modification of eRNAs in cancer remain elusive. Here, we review and synthesize current understanding of the regulatory roles of enhancers, eRNAs, and m6A modifications in cancer. Furthermore, we investigate the possible roles of eRNAs m6A modification in tumorigenesis based on existing literature, offering novel perspectives and directions for future research on epigenetic regulatory mechanisms in cancer cells.